System Dynamics Modeling for Time and Cost Control in Tukad Badung River Infrastructure - Anak Agung Ratu Ritaka Wangsa; Ni Luh Made Ayu Mirayani Pradnyadari; Tjokorda Istri Praganingrum; Ida Bagus Suryatmaja (Universitas Pendidikan Nasional, 2026)
Water infrastructure construction in dense urban environments like Tukad Badung, Denpasar, faces severe operational uncertainty due to weather anomalies. Nonlinear interactions between rainfall, machinery productivity, and labor performance frequently cause schedule delays and cost overruns. This study develops a system dynamics model for adaptive time and cost control in river flood infrastructure projects. Using an exploratory sequential mixed-method design, qualitative expert interviews were transformed into Causal Loop Diagrams (CLD) and quantitative Stock and Flow Diagrams (SFD). Model validation against historical progress data yielded a Mean Absolute Percentage Error (MAPE) of 4.85%, supported by dimensional consistency, extreme-condition, and behavior reproduction tests. Baseline simulations under projected 2026 rainfall indicated a 12-day project delay and a 5.2% cost variance. Policy scenario analysis revealed that the